Default mode network subsystem alterations in obsessive–compulsive disorder. (November 2014) - Beucke, Jan C.; Sepulcre, Jorge; Eldaief, Mark C.; Sebold, Miriam; Kathmann, Norbert; Kaufmann, Christian
Abstract : Background: Although neurobiological models of obsessive–compulsive disorder (OCD) traditionally emphasise the central role of corticostriatal brain regions, studies of default mode network integrity have garnered increasing interest, but have produced conflicting results. Aims: To resolve these discrepant findings by examining the integrity of default mode network subsystems in OCD. Method: Comparison of seed-based resting-state functional connectivity of 11 default mode network components between 46 patients with OCD and 46 controls using functional magnetic resonance imaging. Results: Significantly reduced connectivity within the dorsal medial prefrontal cortex self subsystem was identified in the OCD group, and remained significant after controlling for medication status and life-time history of affective disorders. Further, greater connectivity between the self subsystem and salience and attention networks was observed. Conclusions: Results indicate that people with OCD show abnormalities in a neural system previously associated with self-referential processing in healthy individuals, and suggest the need for examination of dynamic interactions between this default mode network subsystem and other large-scale networks in this disorder.